Sociological Realism: An Islamic Paradigm (American Journal of Islam and Society, 1991)
Ever since its revelation more than fourteen hundred years ago, the Qur’anhas been the object of recitation and memorization, as well as scholarly analysisby millions in every generation. During this long span of time, not onlyreligious scholars and jurists, but also other professionals like physicists,medical doctors, historians, and orientalists have tried to scrutinize and analyzethe Qur’an. It is about time that sociologists paid attention to this primarysource of Islam.Sociological interest in the Qur’an, as belated as it is, is in fact natural,for, after a brief foray in the direction of what one may call Origin IheoZogy,the basic thrust of the Qur’an remains ideological- humanity and its societyin this world. Not that this is such a revealing idea. Whether one looks atit from a juristic point of view or from a historical perspective, it hardlyescapes notice that the Qur’anic verses speak out loudly about the natureof plural living as fabricated by the crisscrossing episodes generated by veryactive, assertive, and expressive individuals over the course of history. Mostof what has been going on in Islamic studies, under the rubric of law andhistory in particular, provides us with sufficient encouragement to cast a freshlook at the same source of knowledge.Questions Sociological Theory Should AnswerAs we have already seen, sociologists have at different times asked differentand disparate, although quite relevant, questions. They have also beeninsufficient questions. For example, symbolic interactionists remained interestedprimarily in the indeterminstic nature of the human act. This microscopicpreoccupation prevented them from asking questions about social processesof a larger magnitude. Even Blumer’s emphasis on collective behavior, whichshowed an early promise for the analysis of revolutionary social change, hashad only scant appeal for his fellow symbolic interactionists.On the other hand, structural-functionalists as well as conflict theoristsremained interested in the deterministic nature of the macro social order ...